JENIS BAMBU DI HUTAN TEMBAWANG DESA SUKA MAJU KECAMATAN SUNGAI BETUNG KABUPATEN BENGKAYANG - Sary, Novia; Fahrizal, .; Yani, Ahmad (JURNAL HUTAN LESTARI, 2018)
Bamboo is a multipurpose plant and occupies a special place in the life of the people of Indonesia. The Village Suka Maju Sub-District Sungai Betung District Bengkayang is one of villages that have bamboo plants that grow wild especially in the forest of tembawang. This study aims to obtain information on the type bamboo in the forest tembawang Village Suka Maju Sub-District Sungai Betung District Bengkayang during 1 month and Â methods used Â is a method exploration with the determination of hide was purposive sampling of double plot measuring 5 m x 5 m, colleting data do with two ways which is : a collection of flora and identification morfologi bamboo, and the kind of data take is primary and secondary. The results of this study found 4 species are: Bamboo Betung (Dendrocalamus asper), Bamboo Tali (Gigantochloa apus), Bamboo Buluh (Schizostzchyum zollingeri Steud) , and Bamboo Munti (Schizostzchyum sp). Bamboo type most commonly found individuals species is the Betung bamboo (Dendrocalamus asper) because the tembawang forest area is located in the hilly area which is the habitat for bamboo betung with its soil type is alluvial.Keywords : Bamboo, Identification, Species